PELATIHAN PEMBUATAN PEWARNA BATIK ALAMI MENGGUNAKAN MESIN PENGADUK MULTIFUNGSI UNTUK UMKM di BEKASI - Cahyati, Sally; Astuti, Pudji; Azmi, Nora; Hadisoebroto, Rositayanti; Putri, Larasati Rizky (Yayasan Education and Social Center, 2023)
Indonesia is the largest batik-producing country in the world. The batik industry is growing rapidly in Indonesia, apart from having a positive impact, there is also a negative impact, namely environmental pollution in waterways and groundwater sources due to liquid waste resulting from batik production. This colored and smelly waste can cause allergies and damage the quality of groundwater which is also a source of drinking water for the surrounding community. Apart from treating wastewater using IPAL, another solution is for batik craftsmen to be motivated and raise awareness to use natural, environmentally friendly dyes. This is what prompted the PKM activity